Gender Relation in Family in Post-COVID-19 Era: Study Among Working Couple in Semarang, Indonesia - Elizabeth, Misbah Zulfa; Safitri, Ririh Megah; Illiyyun, Naili Ni’matul; Masrohatun, Masrohatun; Rahmawati, Titik (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The COVID-19 pandemic which has been running for two years has resulted in changes in work patterns for employees, both private and public. Due to consideration of preventing the spread of the COVID-19 virus, government agencies and private offices are imposing WFH (work from home). As a result, for working couples, the household arena becomes a joint work arena, in which formal and domestic work is carried out. This study aims to discuss the division of labor between husband and wife in the household before the pandemic; the division of labor during the pandemic, and the impact of the division of labor during WFH on the division of labor after the pandemic. The study used qualitative methods and field studies were analyzed using gender theory. Data collection is done by way of interviews, observation and documentation. This research found that there were three trends in relationship changes that were prior to the COVID pandemic, the division of labor was carried out based on the habits that had been built by the couple since they were married, namely families who had a commitment to work together since the beginning of the marriage, so with the pandemic this commitment made it stronger, but for families who do not have a commitment to gender relations, the work arena formed by the pandemic does not really affect gender relations. This finding reinforces the perspective that gender relations are socio-cultural formations so they are not easy to change